Optodinamska analiza pulznih laserskih obdelovalnih procesov z Nd:YAG-laserjem - Strgar, Simon (Materiali in tehnologije, 2001)
Laser drilling and laser marking of metals with a pulsed Nd:YAG laser are discussed. Some characteristics of pulsed-laser processing and the possibilities of process optodynamic analysis are presented for the laser-drilling of aluminium. The optodynamic analysis is based on observation of generated shock waves, which propagate in the material as well as in the surrounding air during laser processing. For the detection of laser-induced shock waves in the air and for measurements of their characteristics the laser-beam deflection probe was used. A linear relation between the shock waves' propagation time and the depth of the laser-drilled holes was found for pulsed-laser drilling of aluminium. For marking purposes the pulse-laser processing system was improved with a communication interface. The preliminary results of laser marking with the introduced advanced system show a significant improvement of marking possibilities.
Keywords: procesi obdelovalni; obdelave laserske; vrtanje; označevanje lasersko; laserji pulzni; laserji Nd-YAG; optodinamika; obdelovalni procesi; kovine; laserska tehnika